Diagnostics and risk factors for bovine respiratory disease - Baruch, Joaquin (Kansas State University, 2020)
Diagnostic inaccuracy and unknown risk distributions for bovine respiratory disease (BRD) are some of the most important issues faced by the feedlot industry. Given these issues, the overarching themes of this thesis are on the evaluation of point-of-care diagnostic methods for BRD and on summarizing, synthesizing, and simulating the impact of risk factors and disease interventions on BRD morbidity. The objectives of the research chapters included in this thesis are to: 1) evaluate BRD disease progression using point-of-care diagnostic methods in a challenge study, 2) map the available literature on risk factors for BRD morbidity in beef cattle using a scoping review, 3) evaluate associations between vaccination programs and BRD morbidity in beef feedlot cattle, and 4) define BRD risk distributions based on cattle characteristics and disease interventions. When evaluating point-of-care diagnostic methods, we observed that computer-aided-stethoscope scores, oxygen saturation levels, and ultrasound-measured consolidation varied by study day and disease stage (viral or bacterial). Clinical illness scores and temperature measurements, commonly used as metrics for BRD diagnosis on the field, did vary by study day but may not be discriminative of disease stage. Lymphocyte, neutrophil, and fibrinogen concentrations, and lymphocyte/neutrophil ratio, demonstrated differences following bacterial inoculation and, therefore, could be used to assess disease progression. Metaphylaxis, vaccination, dietary supplements, and preconditioning programs were the most studied risk factors for BRD morbidity in beef cattle. Although unclear why these risk factors were studied more often than those related to animal management practices, sources of funding, and the potential market value of these interventions seem to be plausible explanations. Vaccination programs for BRD prevention implemented before feedlot arrival were associated with reduced BRD morbidity; however, vaccination programs implemented at feedlot arrival were not. These associations indicate that preconditioning programs, which normally include vaccination before cattle arrive at the feedlot, might be better strategies for reducing BRD’s burden to the beef industry. Metaphylaxis was the most effective intervention at feedlot arrival to reduce BRD morbidity, but its efficacy depended on the antimicrobial drug used and cattle characteristics. The lowest median BRD morbidities were estimated for tilmicosin, gamithromycin, tulathromycin, and tildipirosin, but estimations of BRD morbidity with other antimicrobials were similar to those obtained by feedlot arrival vaccinations on weaned animals. Therefore, whereas metaphylaxis can effectively reduce BRD morbidity, non-antimicrobial alternatives could be implemented to reduce the use of less effective antimicrobials. Overall, the results described in this thesis contribute to improving the knowledge on point-of-care diagnostics methods, availability of data on risk factors for BRD, effectiveness of vaccination timing on BRD morbidity, and defining BRD risk distributions based on cattle characteristics and disease interventions.
Keywords: Bovine respiratory disease; Risk factors; Diagnostics; Vaccination; Risk analysis; Meta-analysis